Bureaucratic Reform of the National Police Agency Through Improving the Quality of Human Resources to Realize Excellent Public Services - Pratama Herry Herlambang; Yos Johan Utama; Aju Putrijanti (Pandecta Research Law Journal, 2023)
The Indonesian National Police (Polri) is a law enforcement agency that is also tasked with maintaining security and protecting the community through public services within the National Police. However, the fact is that the quality of public services in the contemporary era, especially in the National Police Institution, is still relatively low because it is not in accordance with public service standards. Attitudes that tend to be reactive, rigid, and prone to corruption, collusion, and nepotism (KKN) are obstacles and challenges behind the low public trust in the services of the National Police so far. These various factors then became the government's attention to focus on improving the quality of its services through reform of the National Police bureaucracy. This study uses normative-empirical legal research by analyzing and comparing a regulation as a guideline with its implementation based on data on public service standards in the National Police institution. The research aims to obtain results in the form of identifying obstacles and challenges of the National Police in public services to determine the ideal solution through a strategy to strengthen human resources in reforming the National Police bureaucracy to provide excellent public services as one of the implementations of good government to realize professional services and integrity. Human resources are the most important factor; as an apparatus that will execute state administration, it is necessary to strengthen the quality of human resources as an answer to obstacles and challenges in public services in the National Police institution.